Design of the Vacuum Feedthrough for the EAST ICRF Antenna - 杨庆喜 宋云涛 武松涛 赵燕平 (Plasma science & technology, 2011)
Detailed design of the vacuum feedthrough for the ion cyclotron radio frequency （ICRF） antenna in EAST, along with an electro-analysis and thermal structural analysis, is pre- sented. The electric field, the voltage standing wave ratio （VSWR） and the stresses in the vacuum feedthrough are studied. A method using the rings of oxygen-free copper as the cushion and macro- beam plasma arc welding is applied in the assembly to protect the ceramic from being damaged during welding. The vacuum leak test on the prototype of vacuum feedthrough is introduced.